Folfirinox versus gemcitabine/nab-paclitaxel as first-line therapy in patients with metastatic pancreatic cancer: a comparative propensity score study. (September 2019) - Williet, Nicolas; Saint, Angélique; Pointet, Anne-Laure; Tougeron, David; Pernot, Simon; Pozet, Astrid; Bechade, Dominique; Trouilloud, Isabelle; Lourenco, Nelson; Hautefeuille, Vincent; Locher, Christophe; Desrame, Jérome; et al.
Background: Folfirinox (FFX) and gemcitabine/nab-paclitaxel (GN) are both standard first-line treatments in patients with metastatic pancreatic cancer (mPC). However, data comparing these two chemotherapeutic regimens and their sequential use remain scarce. Methods: Data from two independent cohorts enrolling patients treated with FFX ( n  = 107) or GN ( n  = 109) were retrospectively pooled. Primary endpoint was overall survival (OS). Progression-free survival (PFS) was the secondary endpoint. A propensity score based on age, gender, performance status (PS), and presence of liver metastases was used to make groups comparable. Results: In the whole study population, OS was significantly higher in FFX (14 months; 95% CI: 10–21) than in GN groups (9 months; 95% CI: 8–12) before ( p  = 0.008) and after ( p  = 0.021) adjusting for age, number of metastatic sites, liver metastases, peritoneal carcinomatosis and CA19.9 level at baseline. PFS tends to be higher in FFX (6 months) than GN groups (5 months; p  = 0.053). After matching ( n  = 49/group), patients were comparable for all baseline characteristics including PS. In the matched population, there was a trend toward greater OS in patients treated with FFX (HR = 0.67; p  = 0.097). However, survival in each group was not solely a result of the first-line regimen. The proportion of patients who were fit for GN after FFX failure (FFX–GN sequence) was higher (46.9%) than the reverse sequence (20.4%; p  = 0.01), which suggests a higher feasibility for the FFX–GN sequence. Corresponding median OS were 19 months versus 9.5 months, respectively ( p  = 0.094). Conclusion: This study shows greater OS with FFX than with GN in patients with mPC. GN after FFX failure appears more feasible than the reverse sequence.